INSIGHTS INTO LIPID ALTERATIONS FOLLOWING CHEMOTHERAPY IN BREAST CANCER PATIENTS - Zeyad Khalaf Maded (European Science Publishing, 2024)
Postoperative breast cancer (BC) patients may experience changes in serum lipids as a result of breast cancer chemotherapy; however, the precise changes produced by various chemotherapy regimens are not yet known. Aim: The aim of this study was to assess the fluctuations in lipid profile parameters among women with breast cancer who have not undergone treatment compared to those undergoing chemotherapy.
Keywords: Breast cancer; Chemotherapy; Lipid; Cholesterol; TNM.